Analisis Efektivitas Pelatihan Agri-Digital Marketing Pada Pelaku Agribisnis Taratak Paneh - Fachri, Ahmad; Suryani, Nova (Jurnal MeA (Media Agribisnis), 2025)
The development of information and communication technology has driven significant transformation in the agricultural sector, particularly in the marketing aspect. Digital marketing has become an important strategy in expanding market access and increasing the competitiveness of agribusiness products. This study examines the impact of agri-digital marketing training on attitudes knowledge, and skills of agribusiness actors in Taratak Paneh, Korong Gadang Village, Kuranji District, Padang City. The research method used a descriptive quantitative approach with a census technique, involving 31 respondents consisting of agribusiness pioneers, Gen-Z farmers, and MSME managers. Data were collected through questionnaires, interviews, observations, and documentat analysis, then analyzed using descriptive statistics the Wilcoxon T-Test. The results showed a significant increase in all measured indicators. Participants' attitudes increased from 74.99% to 84.76% (+9.77%), knowledge from 73.54% to 81.93% (+8.39%), and skills from 72.73% to 81.69% (+8.96%). These findings indicate that agri-digital marketing training is effectively foster positive attitudes, broadens participants'perspectives, and enchances their practical skills. This is expected to strengthen local economic resilience through the use of inclusive and sustainable technology.